(untitled) (مجلة العلوم الشاملة, 2026)
This conceptual paper identifies the management-related factors influencing universities’ adoption of forensic accounting education (FAE). With the rise of financial fraud, corporate scandals, and digital financial crimes, higher education institutions are increasingly required to equip graduates with investigative and analytical competencies. Despite this growing demand, universities differ significantly in their adoption and implementation of FAE programs. Drawing on the Institutional Theory (IST), Theory of Planned Behavior (TPB), Contingency Theory, and the Health Belief Model (HBM), this study develops a comprehensive framework explaining how internal, external, and normative factors shape university management decisions and behavioral intentions. The paper integrates academic literature and professional resources, and highlighting technological developments while identifying key research gaps, including curriculum inconsistency, technological skill deficits, and lack of practical training. The study contributes to theory and practice by providing insights for university management and policymakers seeking to enhance forensic accounting education.